2020
DOI: 10.1002/csc2.20264
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of benchtop and handheld near‐infrared spectroscopy devices to determine forage nutritive value

Abstract: The quality of predicted plant‐, soil‐, and animal‐response values from near‐infrared (NIR) reflectance spectra depends on the ability to generate appropriate NIR models. The first step in the development of NIR models is collection of spectral data. Limited work, however, has been reported that compares NIR models for prediction of forage nutritive value when the spectra are obtained from devices with different spectral ranges and resolutions. The objectives of this study were to (a) develop and evaluate NIR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
3
22
0
Order By: Relevance
“…In their work using different NIR scanners to predict constituents of grasses and hay, Acosta et al 19 similarly found that while the desktop consistently resulted in superior predictions, handheld NIR developed predictive models were often nearly as precise as desktop NIR devices. While teak foliar nutrient predictions with the desktop were superior, teak growers working with limited budgets, time, and labor may find the handheld spectrometer adequate in predicting foliar nutrient levels of N, P, and K.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their work using different NIR scanners to predict constituents of grasses and hay, Acosta et al 19 similarly found that while the desktop consistently resulted in superior predictions, handheld NIR developed predictive models were often nearly as precise as desktop NIR devices. While teak foliar nutrient predictions with the desktop were superior, teak growers working with limited budgets, time, and labor may find the handheld spectrometer adequate in predicting foliar nutrient levels of N, P, and K.…”
Section: Discussionmentioning
confidence: 99%
“…Model development was performed using a data analysis pipeline written in R environment. 18,19 The pipeline has two separate phases: 1) transformations and outlier detection and 2) model training, crossvalidation, and model selection. The first phase of the program applies mathematical transformations to NIR spectra to remove the scattering of diffuse reflections associated with sample particle size and to improve subsequent regression analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were scanned with a Foss NIRS Model 6500 (Foss North America) and NIRS model development was performed using a data analysis pipeline written in R environment (R Core Team, 2016). The pipeline was previously used in the successful development of NIRS models to determine forage nutritive value of native warm‐season grasses and bermudagrass (Bekewe et al., 2019; Castillo et al., 2020), and to compare predictions among benchtop and handheld NIRS devices (Acosta et al., 2020). To obtain a calibration for CP and ADF, a total of 147 samples (72 samples selected from this trial + 75 samples from bermudagrass trials previously conducted across North Carolina) were assembled into a library, in which both laboratory analyses and NIRS scans were available.…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of CP and ADF were estimated using near infrared spectroscopy (NIRS) models developed for this experiment. Samples were scanned with a Perten DA 7250 NIRS analyzer (PerkinElmer) and NIRS model development was performed using a data analysis pipeline written in R environment (Acosta et al., 2020; R Core Team, 2016). To obtain a calibration for CP and ADF, a total of 169 samples were selected (28% of total samples) for calibration based on their spectral information to represent the population of samples collected in this trial.…”
Section: Methodsmentioning
confidence: 99%